Colonial Road and Irrigation Infrastructure in Kerinci: Civil Engineering, Hydrology, and Environmental Impact Analysis - Faras Puji Azizah; Insira Insani Fitri; Delfi Kurnia Zebua; Yayan Oktiawan; Ilwandri Ilwandri; A'zhami Alim Usman (Tarikhuna: Journal of History and History Education, 2026)
This study discusses the development of road infrastructure and irrigation systems during the Dutch colonial period in Kerinci as part of technical, economic, and spatial management strategies. This study employs a qualitative approach with methods based on digital archives, colonial photographs, historical maps, and academic secondary sources. The data were analyzed through visual interpretation, gravitational hydrology analysis, and tracing the historical context of the development. The results show that the irrigation and road systems built by the colonists were designed using simple yet effective civil engineering principles, such as utilizing natural elevation, reinforcing soil with local materials, and integrating drainage and transportation functions. This infrastructure not only served as a logistics distribution and agricultural irrigation but also as an instrument of territorial control and landscape transformation. This research makes a new contribution by interpreting colonial infrastructure as environmental engineering works that were adaptive to the physical conditions of Kerinci. Thus, this study enriches our understanding of colonial engineering heritage and its relevance to conservation, historical reconstruction of space, and environmental sustainability studies in tropical mountainous regions.